PUBLIC POLICY AND GOVERNANCE FOR STUNTING REDUCTION: LESSONS FROM INDONESIA’S POSYANDU REFORM AND CHINA’S COMMUNITY HEALTH SYSTEM - Nahbisaila Athaya Azzahra; Septiana Dwiputrianti; Tao Wang (Irpia : Jurnal Ilmiah Riset dan Pengembangan, 2025)
This study examines how public policy and governance structures influence the effectiveness of Indonesia’s efforts to reduce stunting through the Posyandu reform under the Six Minimum Service Standards (6 SPM), and identifies relevant lessons from China’s Community Health Service (CHS) system. Using a qualitative descriptive–comparative research design, the study analyzes governance roles, coordination mechanisms, and institutional arrangements based on observations of Posyandu implementation in Bandung Regency and a structured review of China’s CHS model. The findings show that the success of Posyandu reform depends heavily on subnational governance capacity, particularly in coordinating multisectoral programs, ensuring data reliability, and providing clear operational guidance for community health services. Comparative insights from China highlight the value of standardized service packages, professional staffing, and unified data systems in strengthening implementation consistency. The study concludes that governance quality is a central determinant of stunting reduction outcomes and that Indonesia can benefit from adopting selected governance practices from China while maintaining its community-based approach. Future research should incorporate richer empirical data and deeper field-based comparisons.